Enhanced Encapsulation of Linalyl Acetate in Cyclodextrin-Based Metal–Organic Frameworks for Improved Stability - Cheng Zhang; Lirong Zhang; Meiting Zhao; Ning Shao; Shuo Song; Xiaolan Zhu (Molecules, 2025)
Linalyl acetate (LA), a key volatile component in essential oils, is extensively utilized in fragrance, food, and cosmetic industries. Nevertheless, its practical applications are constrained by rapid evaporation and physicochemical instability. This study developed novel cyclodextrin–metal–organic frameworks (CD-MOFs) crystallized from β-cyclodextrin (β-CD) and γ-cyclodextrin (γ-CD) with potassium hydroxide, demonstrating superior structural properties for LA encapsulation. Through comparative analysis with native CDs, the synthesized CD-MOFs exhibited highly ordered crystalline architectures and uniform morphological characteristics. The LA encapsulation capacity of the γ-CD-MOF was systematically evaluated under different conditions using a three-level factorial design via RSM. Optimization revealed maximum encapsulation efficiency (25.9%) under ideal conditions—an LA:γ-CD-MOF mass ratio of 3.8:1, 60.9 °C incubation temperature, and 49.3 min processing time—representing a 2.39-fold enhancement over conventional CD encapsulation. Thermal stability analysis demonstrated remarkable improvement, with LA-γ-CD-MOF complexes showing an onset decomposition temperature of 215 °C, 135 °C higher than that of free LA. Compared with LA-γ-CD, LA coated with γ-CD-MOFs still retained 55.7% at 80 °C for 75 min, with the release rate reduced by about 45.3%. These findings establish the potential of γ-CD-MOFs as effective carriers for thermolabile and volatile compounds in functional food and cosmetic industries.